EMPLOYEE ASSISTANCE PROGRAMMES AND OCCUPATIONAL SOCIAL WORK: INTERRELATED WITH DISTINCT FEATURES - Terblanche, Lourie; Gunya, Thula; Pretorius, Marisa; Maruma, Magalane Reuben; Mbuyisa, Kelebogile; Maseko, Tsholofelo; Mojapelo, Kedibone; Myeni, Nozazi; Tyson, Warren David (Social Work/Maatskaplike Werk, 2021)
A research project was undertaken to explore the differences and similarities between employee assistance programmes (EAPs) and occupational social work (OSW). This was done in order to provide clear and distinct guidelines to potential employers/corporate clients regarding a choice between occupational social work (OSW) and employee assistance programmes (EAP) when they are considering the introduction of programmes and services to promote the psycho-social functioning and productivity of employees and the successful operation of the workplace at large. In addition to the literature study on these two concepts, occupational social work and employee assistance programmes, an empirical study was conducted, consisting of a qualitative and a quantitative component. The qualitative study was performed by a number of researchers who used the same data-collection instrument, developed by the group of researchers under the supervision of the main author of this article. Data were, however, collected in different ways, i.e. one-on-one personal interviews, interviews via e-mail, and focus group interviews. The quantitative part was performed through an on-line survey with a self-developed questionnaire, also under the supervision of the main author. Findings confirmed that both the EAPs and OSW deal with work-related, personal, interpersonal and productivity issues. The findings further confirmed that the kind of employee issues addressed dealt with a range of concerns, including substance abuse, stress, trauma, financial difficulties, conflict, absenteeism, employee development and bereavement. Despite a number of similarities between OSW and EAPs, very few differences have been confirmed other than the variables impacting on structure and legalisation, which also confirms why the EAP and the OSW cannot be used as interchangeable concepts.